Transformation of Accountability in Village Fund Management: Conventional and Sharia Enterprise Model Theory in Samaelo Village, Barebbo District, Bone Regency - Suhaini; Muhammad Fakhri Amir; Musrini Muis (Muhasabatuna : Jurnal Akuntansi Syariah, 2026)
This research aims to analyze the transformation of accountability in village fund management from the conventional model to the Syariah Enterprise Theory (SET) approach in Samaelo Village, Barebbo District, Bone Regency. The focus of this research is to examine the differences in accountability characteristics between the conventional model, which is administrative and regulatory in nature, and the SET approach, which emphasizes spiritual, moral, and social values in village financial management. This research uses a qualitative approach with data collection methods thru in-depth interviews, field observations, and documentation. The informants in this study include the village head, village officials, and the community involved in the village fund management process. The data obtained were analyzed descriptively to fulfilll the form and direction of the accountability transformation that occurs. The research results show that accountability in the conventional model places more emphasis on compliance with formal rules and the preparation of accountability reports. However, this approach does not yet fully reflect the values of substantive transparency and moral responsibility. On the contrary, the application of principles in Syariah Enterprise Theory encourages the realization of more comprehensive accountability, which is not only oriented toward the government and society but also toward spiritual responsibility to God. This transformation is reflected in the increasing awareness of village officials in applying the values of trustworthiness, honesty, justice, and transparency at every stage of village fund management. Based on the research results, it can be concluded that the integration of Sharia values in village fund management can strengthen the quality of accountability comprehensively, both from administrative, social, and spiritual aspects. Therefore, the Sharia Enterprise Theory approach can be used as an alternative in building a more integrity-oriented accountability system that focuses on the welfare of the community.